FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN PUBLIK DI INDONESIA - Biduri, Sarwenda (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2012)
The idea of social responsibility is basically how companies pay attention to the environment, the impacts resulting from the company's operations. Disclosure of corporate social responsibility is proxied by the index of social responsibility refers to the GRI Guidelines. This study examined the effects of four factors of the firm that are the size of the company, profile of the company, the level of leverage, and the size of the board of commissioners on the disclosure of corporate social responsibility. The selection of the sample using purposive sampling method. Population from 388 companies listed on the Indonesia Stock Exchange (BEI) in 2010 and 2011. The sample used some 80 companies. Testing the hypothesis in this study using multiple regression shown that size of the company, profile of the company and the level of leverage influenced disclosure of corporate social responsibility. Unfortunately, the size of the board of commissioners did not influence disclosure of corporate social responsibility